2016
DOI: 10.1016/j.scriptamat.2016.03.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of compositional complexity on the ion-irradiation induced swelling and hardening in Ni-containing equiatomic alloys

Abstract: The impact of compositional complexity on the ion-irradiation induced swelling and hardening is studied in Ni and six Ni-containing equiatomic alloys with face-centered cubic structure. The irradiation resistance at the temperature of 500 °C is improved by controlling the number and, especially, the type of alloying elements. Alloying with Fe and Mn has a stronger influence on swelling reduction than does alloying with Co and Cr. The quinary alloy NiCoFeCrMn, with known excellent mechanical properties, has sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 280 publications
(95 citation statements)
references
References 33 publications
3
90
0
1
Order By: Relevance
“…At the same irradiation dose (50-70 dpa), compared to other commonly-used irradiation-resistant materials, such as M316 stainless steel and pure Zr, an HEA has a relatively-low volume swelling rate [98]. Nagase et al [99] studied the in situ electron irradiation of ZrHfNb with an amorphous structure, and Jin et al [100] studied the CoCrFeNiMn with an FCC structure. It was found that the CoCrFeNiMn HEA did not change significantly after 773 K high-temperature and 3 MeV Ni ions irradiation, and the grains did not coarsen.…”
Section: Irradiation Propertymentioning
confidence: 99%
“…At the same irradiation dose (50-70 dpa), compared to other commonly-used irradiation-resistant materials, such as M316 stainless steel and pure Zr, an HEA has a relatively-low volume swelling rate [98]. Nagase et al [99] studied the in situ electron irradiation of ZrHfNb with an amorphous structure, and Jin et al [100] studied the CoCrFeNiMn with an FCC structure. It was found that the CoCrFeNiMn HEA did not change significantly after 773 K high-temperature and 3 MeV Ni ions irradiation, and the grains did not coarsen.…”
Section: Irradiation Propertymentioning
confidence: 99%
“…Comparisons on the irradiation induced swelling up to 53 dpa have been made between Ni and a series of Ni-containing FCC SP-CSAs in single crystalline form at 500 • C using stepheight measurements (Jin et al, 2016c). Pure Ni has shown >6% overall swelling at this condition.…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 99%
“…Note that irradiation temperature is a critical parameter for high temperature irradiation induced effects, e.g., swelling, and the temperature dependence varies with alloy compositions. The experimental studies till present primarily have focused either on one HEA at different irradiation temperatures (Kumar et al, 2016;Yang et al, 2018) or on the effects of compositional complexity at single irradiation temperature (Jin et al, 2016c;Lu et al, 2016b). How the number and species of principal alloying elements affect the temperature dependence of irradiation response in SP-CSAs requires future systematic studies.…”
Section: Response To the Irradiations At Elevated Temperaturesmentioning
confidence: 99%
“…The complicated random arrangement of alloying elements and local chemical environment at atomic level lead SP-CSAs to exhibit extraordinary properties compared with traditional alloys, such as high thermal stability and hardness, high strength-to-weight ratio, high-temperature strength, great wear and fatigue resistance, and also excellent corrosion resistance13141516. In addition, the high-level site-to-site lattice distortions and compositional complexities in SP-CSAs can effectively reduce the mean free path of electrons, phonons and magnons; these distortions and complexities can also be used to modify formation energies, migration barriers and diffusion pathways of irradiation-induced defects, thereby modifying defect generation, interaction, interstitial–vacancy recombination in the early stages of irradiation17181920. A recently published paper indicates that equiatomic alloys may be more resistant to radiation damage than the corresponding pure elements21.…”
mentioning
confidence: 99%